Gender Identity and Agency of Women in a Higher Education Institution - Dr. Suha Alhothali (Journal of Educational and Human Sciences, 2023)
In higher education institutions, we find that there is a dearth of women in decision-making positions. Public universities, as an example, promote the gender roles of both men and women. This research examined the gender performativity of six female faculty members at a Saudi public university. using a methodology of a qualitative case study, utilizing methods of interviews, observations, and documentation. In this research, I answered the question of how do female faculty members perform their gender at their university? I utilized the theory of gender performativity to answer this question. Gender performativity theory believes that, gender is socially constructed through gendered performances. The theory helped to understand why female faculty members build and maintain gender norms in the university. Moreover, the research exposed the effect of gender performativity on how the job opportunities distributed in the women’s workplace. The. findings were mainly in the areas of: (1) gender identity; (2) women’s agency; (3) and regulatory power.